2006
DOI: 10.1172/jci28775
|View full text |Cite
|
Sign up to set email alerts
|

PLCγ2 regulates osteoclastogenesis via its interaction with ITAM proteins and GAB2

Abstract: Excessive bone loss in arthritic diseases is mostly due to abnormal activation of the immune system leading to stimulation of osteoclasts. While phospholipase Cγ (PLCγ) isoforms are known modulators of T and B lymphocyte-mediated immune responses, we found that blockade of PLCγ enzymatic activity also blocks early osteoclast development and function. Importantly, targeted deletion of Plcg2 in mice led to an osteopetrotic phenotype. PLCγ2, independent of PLCγ1, was required for receptor activator of NF-κB ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
250
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 207 publications
(265 citation statements)
references
References 54 publications
14
250
0
1
Order By: Relevance
“…It has been reported that RANK associates with Gab2 and PLCγ2 upon RANKL stimulation [10,11,20]. As our data indicate that EEIG1 physically interacts with RANK, we asked whether endogenous EEIG1, Gab2 and PLCγ2 form complexes with RANK.…”
Section: Rankl Induces the Formation Of A Complex Containing Rank Eementioning
confidence: 83%
See 4 more Smart Citations
“…It has been reported that RANK associates with Gab2 and PLCγ2 upon RANKL stimulation [10,11,20]. As our data indicate that EEIG1 physically interacts with RANK, we asked whether endogenous EEIG1, Gab2 and PLCγ2 form complexes with RANK.…”
Section: Rankl Induces the Formation Of A Complex Containing Rank Eementioning
confidence: 83%
“…It has become clear that RANK transduces key signals by directly interacting with TRAF6 [24,25]. In addition, it has been reported that PLCγ2 binds to Gab2 in response to RANKL, mediates Gab2 recruitment to RANK, and is required for osteoclast formation [10,20]. Moreover, PLCγ2 and Tec/ Btk kinases are activated by RANK and ITAM signals, thereby activating calcium signaling required for the induction of NFATc1, the key transcription factor for osteoclast differentiation [11,16,26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations